Individual and collaborative infographic design and cognitive strategies in visual literacy support process: a qualitative research perspective - Özer Şanal, Seda; Torun, Fulya (Routledge, 2024)
This study examined the individual and collaborative infographic development processes of middle school students in a qualitative research context. In the first phase, individual and collaborative infographics were developed, a simultaneous think-aloud protocol and interviews were conducted. In the second phase, focus group interviews were conducted with 22 teachers. The findings of the study revealed that students who developed infographics individually and collaboratively completed their tasks at different stages. Protocol analysis data showed that individual and collaborative efforts were reflected in cognitive processes and that collaborative groups spent less time in testing and individual students spent less time in questioning. The findings showed that collaborative learning activities can support the learning process with components such as questioning, peer scaffolding, and sharing. © 2024 International Visual Literacy Association.
Keywords: collaboration; concurrent think aloud; infographic; secondary education; Visual literacy